ABOUT THE EQUIVALENCE OF PHRASES IN THE WORK GONE WITH THE WIND WITH EXPRESSIONS IN THE UZBEK LANGUAGE (American Journal of Interdisciplinary Research and Development, 2023)
This article is devoted to the functional-discursive analiysis of phraseological units in the work of Margaret Mitchells Gone with the Wind.